2018
DOI: 10.3892/mmr.2018.8830
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the tumor‑suppressive function of circular RNA FOXO3 in non‑small cell lung cancer through sponging miR‑155

Abstract: Circular RNAs (circRNAs) are a class of endogenous noncoding RNAs that have been demonstrated to be potential regulators in the development and progression of various types of human cancer. However, little is known about their roles in cancer initiation and progression, particular in non-small cell lung cancer (NSCLC). In the present study, the expression level of circRNA-forkhead box O3 class (FOXO3) in NSCLC specimens was determined and its functional role was investigated in NSCLC cells. By performing Taq-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 28 publications
6
77
2
Order By: Relevance
“…Accumulating studies showed that circFOXO3 was involved in progression of diseases, such as cardiac senescence 21 and nonsmall-cell lung cancer. 22 Moreover, Burton Yang et al reported circFOXO3 interacted with p21 and CDK2, and retarded cell cycle progression. 15 They also detected that circFOXO3 induced tumour apoptosis though enhancing FOXO3 activity.…”
Section: Slc25a15 Was Up-regulated In Pca Tissuesmentioning
confidence: 99%
“…Accumulating studies showed that circFOXO3 was involved in progression of diseases, such as cardiac senescence 21 and nonsmall-cell lung cancer. 22 Moreover, Burton Yang et al reported circFOXO3 interacted with p21 and CDK2, and retarded cell cycle progression. 15 They also detected that circFOXO3 induced tumour apoptosis though enhancing FOXO3 activity.…”
Section: Slc25a15 Was Up-regulated In Pca Tissuesmentioning
confidence: 99%
“…After abstract and full article review, 24 published articles were enrolled for the final analysis. Among them, 5 articles investigated diagnostic value of circRNAs in lung cancer [24,[33][34][35][36], and 19 studies examined prognostic information related to overall survival [32,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The period of the eligible studies ranged from 2017 to 2018 with a total of 2122 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…CircRNAs Are Diagnostic Biomarkers for Lung Cancer. We retrieved 5 published articles pertaining to the expression levels of different circRNAs in human lung cancer, including 1 downregulated circRNA [24] and 4 upregulated circRNAs [33][34][35][36]. Furthermore, in the selection process for eligible articles, results of studies were considered acceptable only based on the expression of circRNAs in tissue, while consequences of studies based on the expression levels of circRNAs in serum, plasma, or peripheral blood samples were not taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations